1985
DOI: 10.1042/bj2250195
|View full text |Cite
|
Sign up to set email alerts
|

The molecular structure and lubricating activity of lubricin isolated from bovine and human synovial fluids

Abstract: Lubricin was isolated from bovine ankle, metacarpophalangeal and knee and human knee synovial fluids. The lubricins isolated from the bovine joint fluids had the same amino acid and carbohydrate compositions, but differences were observed in the relative molecular masses. The Mr values of bovine metacarpophalangeal and ankle lubricin determined by light-scattering measurements were about 200 000, whereas values of 132 000 and 143 000 were obtained for the bovine knee lubricin. The human knee lubricin had a sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
183
0
6

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(195 citation statements)
references
References 10 publications
6
183
0
6
Order By: Relevance
“…Boundary lubrication is one mechanism by which the articular surface of cartilage provides low-friction properties, and is mediated in part by proteoglycan 4 (PRG4) molecules, [1][2][3][4] found both in synovial fluid (SF) and in a layer bound to the articular cartilage surface. 5 In classical descriptions of lubrication modes, boundary lubrication during surface-to-surface contact is mediated by a molecular surface layer or film attached to one or both surfaces, 6 suggesting that the PRG4 bound to the articular cartilage surface mediates boundary lubrication function in the joint.…”
Section: Introductionmentioning
confidence: 99%
“…Boundary lubrication is one mechanism by which the articular surface of cartilage provides low-friction properties, and is mediated in part by proteoglycan 4 (PRG4) molecules, [1][2][3][4] found both in synovial fluid (SF) and in a layer bound to the articular cartilage surface. 5 In classical descriptions of lubrication modes, boundary lubrication during surface-to-surface contact is mediated by a molecular surface layer or film attached to one or both surfaces, 6 suggesting that the PRG4 bound to the articular cartilage surface mediates boundary lubrication function in the joint.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][9][10][11][12] It has the same lubricating properties as normal synovial fluid. [9][10][11][12] Lubricin also stimulates growth of megakaryocyte colonies in vitro. 8 Loss-of-function mutations in lubricin causes camptodactyly-arthropathy-coxa varapericarditis syndrome (CACP).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Such molecules may lubricate the interfaces among bundles of collagen fibrils to facilitate the sliding of structures such as the fascicles of tendons. 7 Although earlier work suggested that glycosaminoglycans (GAGs) may be serving in this capacity, 8 more recent investigations have indicated that a lubricating glycoprotein is responsible for the tribology of the internal structures of musculoskeletal tissues.…”
mentioning
confidence: 99%